THE EFECTIVENESS OF USING BLENDED LEARNING TOWARD STUDENTS’ VOCABULARY MASTERY - Diyah Dwi Agustina (Universitas Nahdlatul Ulama Lampung, 2019)
This experimental research presented Blended learning for the vocabulary mastery faced by the students of Primary School Teacher Education. The objective of this research is to know whether there is influence of using Blended Learning toward the students’ vocabulary mastery and to know whether Blended Learning giving the positive influence to the students’ vocabulary mastery. The method of investigation is held through quantitative research. The researcher uses queasy experimental research. The research is conducted at the students in second semester of Primary School Teacher Education in 2019. The population in this research is 12 classes. The researcher takes the sample, 35 students as experiment class and 35 as control class based on classification of student level. The researcher uses cluster sampling as technique sampling. For analyzing the data, the researcher uses T test formula. The researcher got the result of ratio is 4,71 and ttable is 2,44. It means that tcount > ttable. So, there is positive influence of using Blended Learning toward the students’ vocabulary mastery at the second semester of Primary School Teacher Education UNU Lampung in 2019.The researcher expects English teacher to use blended learning in teaching vocabulary. Key words: experimental research, blended learning, vocabulary mastery